DECISION SUPPORT SYSTEM SELECTION OF DEPARTMENT AT TELKOM VOCATIONAL SCHOOL, LAMPUNG USING THE TOPSIS METHOD - Arjuna Primanada (SRA Publishing, 2022)
In this era of technology, information technology is developing rapidly. One of them is in the field of education, for now there are many learning media that already use technology as a means to make it easier. With the fundamental changes in the field of information and communication technology, information has now become a very valuable and decisive commodity to achieve success. The problem raised this time is how to determine the majors that match the abilities of new students at SMK Telkom Lampung. Because in the activity of determining the majors at SMK Telkom Lampung. The school has not implemented a computerized system optimally because the majority of majors are still using a manual system. On this occasion the method that will be used to assist in the selection of majors at SMK Telkom Lampung is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The TOPSIS method is based on the concept that the best selected alternative not only has the shortest distance from the positive ideal solution, but also has the longest distance from the negative ideal solution. The TOPSIS method also has a simple and relatively easy-to-understand concept, is computationally efficient, and has the ability to measure the relative performance of each decision alternative in a simple mathematical form. In applying the selection of majors using the Decision Support System, it is hoped that it can really help facilitate and make the desired results in selecting majors more accurate, save time and get results faster. The decision support system for selecting majors at SMK Telkom Lampung can be further developed by creating a system where each test result that becomes a criterion is directly connected to the decision support system for selecting this major.